2014
DOI: 10.1155/2014/820524
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Vitamin D Metabolites on Plasma Cytokine Concentrations in Endurance Sport Athletes and on Multiantigen Stimulated Cytokine Production by Whole Blood and Peripheral Blood Mononuclear Cell Cultures

Abstract: Aim. Our aims were to determine the influence of plasma total 25-hydroxy vitamin D (25(OH)D) status on the plasma cytokine concentrations in athletes and the in vitro effects of different doses of 1, 25 dihydroxyvitamin D3 (1, 25(OH)2D3) on multiantigen stimulated cytokine production by whole blood and peripheral blood mononuclear cell (PBMC) cultures. Methods. Plasma samples from 43 athletes with high and low levels of 25(OH)D were assayed for the concentrations of cytokines. The whole blood samples and PBMCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…The findings of our study are consistent with what He et al [21] reported in their study. They cultured both whole blood and PBMCs in presence and absence of vitamin D but used a multi-antigen vaccine containing tetanus, Haemophilus influenzae type b, diphtheria, poliomyelitis and acellular pertussis antigens as a stimulant and assessed the use of different vitamin D concentrations in the culture of six samples.…”
Section: Discussionsupporting
confidence: 94%
“…The findings of our study are consistent with what He et al [21] reported in their study. They cultured both whole blood and PBMCs in presence and absence of vitamin D but used a multi-antigen vaccine containing tetanus, Haemophilus influenzae type b, diphtheria, poliomyelitis and acellular pertussis antigens as a stimulant and assessed the use of different vitamin D concentrations in the culture of six samples.…”
Section: Discussionsupporting
confidence: 94%
“…This decrease in vitamin D was accompanied with a slight decrease in sIgA concentration ( d = 0.23) only in the SL group over weeks of training. This result is in conformity with previous studies reporting a positive correlation between the vitamin D status and the sIgA secretion (He et al 2014 ). However, it is worth noting that the decrease in vitamin D could have been also induced by the low direct exposition to UVB, since this study was conducted in the winter season at a high latitude (Paris, 53°N).…”
Section: Discussionsupporting
confidence: 94%
“…A recent study in endurance athletes demonstrated that vitamin D insufficiency associated with a decrease in IFN-c while 1,25(OH)D inhibited IFN-c production by peripheral blood mononuclear cells [39]. This paradox suggests a pro-inflammatory cytokine decrease with low 25(OH)D and following 1,25(OH)D exposure, thereby underscoring the complexity of investigating the influence of vitamin D on cytokines and extrapolating in vitro results to in vivo conditions.…”
Section: Discussionmentioning
confidence: 99%